Experimental investigation of a CO2-based Transcritical Rankine Cycle (CTRC) for exhaust gas recovery. (15th December 2018) - Shi, Lingfeng; Shu, Gequn; Tian, Hua; Huang, Guangdai; Li, Xiaoya; Chen, Tianyu; Li, Ligeng
Abstract: CO2 -based Transcritical Rankine Cycle (CTRC) system has attracted more and more attention for exhaust gas recovery currently due to CO2 's environmental and stable performance, as well as the miniaturization potential of components. Among the CTRC researches, parameters analysis is an eternal theme, and turbine inlet pressure and temperature are the focus. In real operation, the temperature is mainly influenced by pump speed. In this study, various operating pressure and various pump speed of a CTRC test bench were set for a parameter analysis. Two configurations were considered at a constant engine condition, basic CTRC (B-CTRC) and regenerated CTRC (R-CTRC). After measuring parameters (e.g. pressure, temperature, mass flow rate), heat absorption quantity was calculated, while net power output, thermal efficiency, exergy efficiency were estimated. Results showed that the pressure ratio had significantly positive impact on the CTRC performance. And the law for the effect of mass flow rate was not obvious. The R-CTRC can realize 42.4%, 71% and 48.9% improvement of net power output, thermal efficiency and exergy efficiency relative to the B-CTRC. After the parameter analysis, the optimal condition based on the maximum net power output was predicted by the regression of experimental data. Highlights: Experimental analysis of pump speed and pressure ratio. High pump speed accelerates reduction speed of CO2 flow rate with pressure ratio. Regenerator improves CTRC performance form energy and exergy analysis. Optimal condition obtained by regression model.